MED12 mutations and NOTCH signalling in chronic lymphocytic leukaemia - Wu, Bian; Słabicki, Mikołaj; Sellner, Leopold; Dietrich, Sascha; Liu, Xiyang; Jethwa, Alexander; Hüllein, Jennifer; Walther, Tatjana; Wagner, Lena; Zenz, Thorsten (British journal of haematology, 2017)
Mutations in the N-terminus of MED12 protein occur at high frequency in uterine leiomyomas and breast fibroepithelial tumours, and are frequently found in chronic lymphocytic leukaemia (CLL). MED12 mutations have been previously linked to aberrant Cyclin C-CDK8 kinase activity, but the exact oncogenic function in CLL is unknown. Here, we characterized MED12 mutations in CLL and identified recurrent mutations in 13 out of 188 CLL patients (6·9%), which clustered in the N-terminus. MED12 mutations were associated with unmutated IGHV (P = 0·024). Protein analysis of NOTCH1 in primary CLL samples revealed increased levels of NOTCH1 intracellular domain (NICD), the active form of NOTCH1, in the context of MED12 mutations. We found evidence that NICD is the target of Cyclin C-CDK8 kinase using a specific CDK8 inhibitor. In line with these findings, MED12 mutations were mutually exclusive to mutations in NOTCH1 in CLL, based on a meta-analysis of 1429 CLL patients (P = 0·011). Our results suggest that MED12 mutations may contribute to CLL pathogenesis by activating NOTCH signalling.